Aboriginal settlement patterns in the upper Stikine River drainage, northwestern British Columbia - Friesen, David E. (University of Calgary, 1985)
Bibliography: p. 174-192. This thesis focusses on aboriginal settlement patterns in the Upper Stikine River drainage, northwestern British Columbia. Utilizing an ecological approach to investigate this problem, palaeoenvironmental and archaeological field work were conducted on the Spatsizi and Klastline Plateaux. The objective was to evaluate a series of hypotheses concerning the interrelationship between culture and environment over the last 3,000 years. These test hypotheses were formulated from information supplied by an ethnographic model of subsistence (Albright 1982) and, environmental and archaeological studies conducted in the region. Palynological evidence suggests that the research area is characterized by environmental stability during this time period. Therefore, it was assumed that the effective resource base has not changed. Archaeological investigations resulted in discovery of 67 prehistoric sites. The locations of these sites are influenced by local, regional and seasonal variations in the resource base. Settlement locations are oriented to forest/aquatic ecotonal communities where human accessibility to a range of important fixed (ie., landform, water source etc.) and mobile (ie., ungulate populations} resources is maximized. Site density in the study area is low (0.15 - 1. 1 km^2) as local aboriginal populations tended to exploit dispersed and mobile resources such as caribou. Sites recorded are generally small and transitory, representative of short-term occupations by small hunting parties. Seasonal changes in resource abundance and availability forced frequent camp relocation, as well as changes in group size. Therefore, settlement mobility and flexibility of social organization were strategies employed to cope with resource variability and unpredictability. Techniques employed to exploit resources were simple, characterized by relatively homogeneous tool assemblages dominated by obsidian flakes. Palaeoenvironmental, archaeological and historic evidence suggest that fire was an important ...